2010
DOI: 10.1007/s00125-010-1789-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimal antiproteinuric dose of aliskiren in type 2 diabetes mellitus: a randomised crossover trial

Abstract: Aim The optimal antiproteinuric dose of aliskiren is unknown. This study compared the effect of placebo and increasing doses of aliskiren on urinary albumin excretion rate (UAER). Methods The trial was a double-blind crossover design. Twenty-six patients with type 2 diabetes mellitus, hypertension and albuminuria were randomised to 2-month treatments with placebo or aliskiren 150 mg, 300 mg or 600 mg once daily, in random order. Primary endpoint was change in UAER; secondary endpoints included changes in 24-h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…13 Several small studies with aliskiren in diabetes have demonstrated an antiproteinuric effect of monotherapy, enhanced albuminuria reduction with dual RAAS blockade and that the optimal dose for reno-protection is 300 mg once daily. [14][15][16] In a multinational, randomized, double-blind study (AVOID), in 599 patients with hypertension, type 2 diabetes and nephropathy, who are receiving the recommended renoprotective treatment, we showed that the anti-proteinuric effect of aliskiren was independent of its blood pressure-lowering action. 17 The aim of the present trial is to determine the effectiveness and safety of direct renin inhibition with aliskiren compared with placebo in type 2 diabetic patients at high risk of fatal and non-fatal renal and CVD events.…”
Section: Introductionmentioning
confidence: 99%
“…13 Several small studies with aliskiren in diabetes have demonstrated an antiproteinuric effect of monotherapy, enhanced albuminuria reduction with dual RAAS blockade and that the optimal dose for reno-protection is 300 mg once daily. [14][15][16] In a multinational, randomized, double-blind study (AVOID), in 599 patients with hypertension, type 2 diabetes and nephropathy, who are receiving the recommended renoprotective treatment, we showed that the anti-proteinuric effect of aliskiren was independent of its blood pressure-lowering action. 17 The aim of the present trial is to determine the effectiveness and safety of direct renin inhibition with aliskiren compared with placebo in type 2 diabetic patients at high risk of fatal and non-fatal renal and CVD events.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in exposure did not correlate with the severity of renal insufficiency, as assessed by CL CR [19]. The accumulation of aliskiren at steady state (indicated by the AUC from 0 and 24 hours [AUC 24 ] on day 7 vs day 1) was similar in healthy subjects (1.79) and each subgroup of subjects with renal impairment (1.39-1.99). The authors conclude that exposure to aliskiren is increased by renal impairment, but does not correlate with the severity of renal insufficiency (CL CR ); therefore, adjustment of the starting dose of aliskiren is not required in patients with renal impairment [19].…”
Section: Pharmacology Of Aliskirenmentioning
confidence: 88%
“…Additionally, 65% patients achieved blood pressure response (mean DBP < 90 or a 10 mmHg decrease, or mean SBP < 140 or a 20 mmHg decrease), and 30% achieved blood pressure control (mean SBP < 140 mmHg and mean DBP < 90mmHg) at the week 8 endpoint [23]. Persson et al [24] examined the antiproteinuric effect of increasing doses of aliskiren (up to 600 mg) in hypertensive patients with diabetic nephropathy (eGFR: 85 mL/min/1.73 m 2 ). Treatment with aliskiren 150, 300 and 600 mg daily reduced urinary albumin excretion rate by 36, 48 and 52%, and 24 h SBP by 4.5, 8.0 and 9.2 mmHg, respectively, compared with placebo.…”
Section: Pharmacology Of Aliskirenmentioning
confidence: 99%
See 1 more Smart Citation
“…Aliskiren 150, 300 and 600 mg reduced UAER significantly by 36%, 48% and 52% respectively compared with placebo 26 Persson et al [93] 2010…”
Section: Safety Studiesmentioning
confidence: 99%